Faktor yang Berhubungan dengan Penggunaan Skrining Riwayat Kesehatan Digital BPJS Kesehatan di Puskesmas Gambir, Jakarta Pusat - Devina Ula Adzra (Jurnal Medika Nusantara, 2025)
The target achievement for Health History Screening (SRK) of BPJS Kesehatan in Central Jakarta in 2023 was set at 244,620 SRK annually. Among the eight sub-district health centers in Central Jakarta, Gambir Health Center ranked last, achieving a target of 36,654 SRK (79,23%) out of the expected 46.260. The purpose of this study was to determine the factors associated with the use of BPJS digital health history screening among JKN participants at Gambir Health Center, Central Jakarta. This study employed a quantitative method with a cross-sectional design. The research was conducted on October-November 2024, and data collection used primary data through questionnaires. The sample consisted of 110 JKN participants, selected using a purposive sampling technique. Data were analyzed using univariate analysis, bivariate analysis with chi-square tests, and multivariate analysis with logistic regression. The results showed that the variables associated with the use of BPJS digital health history screening included age (p<0,01), education (p=0,03), marital status (p<0,01), predicted time duration (p<0,01), gadget ownership (p<0,01), and participants' attitudes (p=0,03). The significant factor influencing the use of BPJS digital health history screening was gadget ownership.